The Political Role of the Military Institution in West African Countries( Determinants and Mechanisms) (قضايا سياسية, 2024)
During the period following independence, the military governments in West Africa were incapable of meeting the economic social and security requirements of their citizens This was primarily due to their tendency to endorse the authority and influence of specific ethnic and tribal groups within the military and in positions of power both within the country and internationally The West African area continued to be a focal point for military involvement. From the late sixties to the early nineties of the twentieth century the region experienced a period of political turmoil characterised by the over throw of governments led by personal authoritarian and corrupt regimes This trend continued until the second decade of the twenty-first century, during which the West African region remained a hub for military intervention in politics and the removal of governments with such characteristics. This situation persisted from the late 1960s to the early 1990s during which this region experienced a transition to civilian political governance and elected administrations This continued until the 2010s when many of these elected regimes lost their ability to convincingly maintain their democratic legitimacy. This was due to pervasive political corruption among the ruling elites manipulation of constitutional provisions governing the peaceful transfer of power and growing alienation between governments and political and civil factions This resulted in the formation of a pernicious cycle often referred to as the coup trap.